1998
DOI: 10.1002/j.2161-1912.1998.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment and Coping Styles of Urban African American High School Students

Abstract: In a study of African American (n = 208) urban high school students, grade point average (GPA) and specific strategies for coping with day-to-day stressors were found to be significantly related to psychological adjustment. Students who had higher GPAs tended to use family members as a means of solving problems, minimized problems by the use of humor, and used relaxation activities less often were found to have the most positive psychological adjustment, as measured by the index score of the Affects Balance Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…For securely attached adolescents stress appears to trigger increases in family communication and decreases in negative avoidance coping. These findings are consistent with past studies showing that secure individuals seek and accept interpersonal support (e.g., Armsden & Greenberg, 1987;Shulman, 1993;Simpson et al, 1992) as well as studies that show that effective coping predicts psychological adjustment (Steward et al, 1998). Insecurely attached individuals tend to avoid positive coping strategies, possibly because they lack trust in others, feel unworthy of support, don't recognize the need for support, or are conflicted about seeking it (Simpson et al, 1992;Simpson & Rholes, 1994).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For securely attached adolescents stress appears to trigger increases in family communication and decreases in negative avoidance coping. These findings are consistent with past studies showing that secure individuals seek and accept interpersonal support (e.g., Armsden & Greenberg, 1987;Shulman, 1993;Simpson et al, 1992) as well as studies that show that effective coping predicts psychological adjustment (Steward et al, 1998). Insecurely attached individuals tend to avoid positive coping strategies, possibly because they lack trust in others, feel unworthy of support, don't recognize the need for support, or are conflicted about seeking it (Simpson et al, 1992;Simpson & Rholes, 1994).…”
Section: Discussionsupporting
confidence: 86%
“…Both attachment and coping involve cognitive interpretations of stressful events and decisions regarding how much trust to place in self and others. Secure children may be viewed as using more effective coping mechanisms and thereby perceiving less stress impact compared to less secure children (Compas, 1988;Steward et al, 1998).…”
mentioning
confidence: 98%
“…The two basic coping strategies subsumed within this variable included cognitive decision making and direct problem solving. Cognitive decision making is similar to that of planning, which has been associated with increased positive affective experiences in samples of college students and adolescents (Steward et al, 1998; Vaughn & Roesch, 2003). The use of direct problem solving has also been associated with more positive affective experiences (Aldridge & Roesch, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, African American male youth have been shown to suppress their anger to cope with social challenges (Johnson & Greene, 1991;Stevenson, 2002). Another strategy is for African American youth to use "role-flexing," or the hypervigilant altering of one's speech, behavior, or appearance (such as speaking softly, using humor, and taking care not to make sudden movements) to appear nonthreatening, diminish the effects of negative stereotypes, and gain social acceptance (Franklin & Boyd-Franklin, 2000;Steward et al, 1998). For example, Steward et al (1998) found that, among African American high-school students, horseplay and class clowning were significantly related to their psychological adjustment in otherwise hostile social situations.…”
Section: Teacher Perceptions and Student Behavioral Outcomesmentioning
confidence: 99%